Desinstitucionalização prisional e o discurso do método APAC - Juliana Marques Resende (2013)
This thesis has been developed about prison deinstitutionalization and the discourse of the APAC method. For this we rely on the concept of deinstitutionalization, brought by the psychiatric reform, which considers that this process is a dismantle, a transformation of power relations already encoded and crystallized. Covering not only the transformation of the prison institution of APAC, but also the institution of imprisonment as a penalty. Here is the historical context of the institutionalization of prisons as punishment and also the emergence of the APAC method as an alternative to the criminal justice system in Brazil .The APAC method brings up a Christian proposal, which also relies on ensuring the rights of people arrested. To conduct the survey, we adopted the method of critical discourse analysis that is based mainly in the method of discourse analysis proposed by Michel Foucault. We also used the genealogy perspective, because we understand that they are complementary methodologies. The corpus of the research was the book "Ninguém é irrecuperável. APAC: A revolução do sistema penitenciário"* written by Mario Ottoboni. Through genealogy, we understand also the institutionalization of the ideal of rehabilitation contained in imprisonment and, through this route, we identify the most influential ideologies of this ideal. From these ideologies we have created the categories;** religion, law and management. These categories guided the creation and analysis of the statement contained in the corpus analyzed. Results allowed to reflect on the reproduction of ideologies contained in the discourse of rehabilitation, where religion dominates as the main proposal and also the vision of pathologizing people arrested. We also see that the method APAC brings advancements to ensure the rights of people arrested and, through some practices, denaturalizes prison violence. However, when it comes to deinstitutionalize prisons as punishment, the APAC method comes against, saying it can help to change people through prison.